2018
DOI: 10.1002/tal.1498
|View full text |Cite
|
Sign up to set email alerts
|

Damage‐controlled performance‐based design optimization of steel moment frames

Abstract: In the present paper, performance-based design of steel moment-resisting frames (SMRFs) is implemented to minimize total cost of the structures. The total cost is summation of the initial construction cost and the seismic damage cost in operational lifetime of the structures subjected to seismic loading. In order to evaluate the seismic damage cost, Park-Ang damage index (DI), as one of the most realistic measures of structural seismic damage, is utilized. To calculate the DI, nonlinear time-history response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Therefore, it is necessary to analyze the seismic fragility of the GSPC walls from a probabilistic perspective. Seismic vulnerability analysis can comprehensively evaluate the seismic performance of structures by calculating the conditional probabilities of different damage levels under different earthquake intensities 20–22 . In this section, the seismic fragility analysis based on the incremental dynamic analysis method (IDA) for the structures in Case 2 (FCW‐RC and FCW‐GS structures) was carried out.…”
Section: Fragility Evaluationsmentioning
confidence: 99%
“…Therefore, it is necessary to analyze the seismic fragility of the GSPC walls from a probabilistic perspective. Seismic vulnerability analysis can comprehensively evaluate the seismic performance of structures by calculating the conditional probabilities of different damage levels under different earthquake intensities 20–22 . In this section, the seismic fragility analysis based on the incremental dynamic analysis method (IDA) for the structures in Case 2 (FCW‐RC and FCW‐GS structures) was carried out.…”
Section: Fragility Evaluationsmentioning
confidence: 99%
“…As opposed to PBOSD, which can lead to highly vulnerable designs against uncertainties, the RBOSD method led to safe and reliable designs for RC frames. Fattahi and Gholizadeh [ 18 ] proposed designing SMRFs with damage‐controlled performance‐based on structural optimization. The design results indicated that the collapse margin ratio (CMR), damage measure ratio, and degree of repairability are increased.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [18] introduced an index to compute the amount of structural damage using the force analogy method. Gholizadeh and Fattahi [19] studied the damage parameter for an optimally designed steel moment frame. Danesh et al [20] evaluated the seismic collapse capacity of a steel moment frame optimized using performance-based design optimization.…”
Section: Introductionmentioning
confidence: 99%